FAZ DEĞİŞTİRİCİ MADDELER VE UYGULAMALARI - ACAR, SÜREYYA ŞEYMA (Fırat Üniveristesi, 2014)
İki aşamada gerçekleştirilen bu çalışmanın ilk aşamasında Kamfen, stearik asit ve palmitik asit maddeleri kullanılarak farklı oranlarda Kamfen-palmitik asit ve Kamfen-stearik asit seri karışımları hazırlandı. Hazırlanan bu iki seri FDM özellikli ötektik karışımdan yapısal ve termal özelliği en iyi olan karışımlar ana karışım olarak belirlendi. İkinci basamağında uçucu kül, proklastik mermer tozu ve barit seçilen karışımlara katkılandırıldı. Elde edilen kompozit temelli FDM'lerin yapısal ve temel özellikleri DSC, FT-IR, TGA ve SEM teknikleri kullanılarak analiz edildi.

In the first step of the work, which are placed in two steps, camphene-palmitic and camphene-stearic acid and mixtures have been prepared by using camphene, stearic acid and palmitic acid with different rates. The main eutectic mixtures have been selected from these prepared two series which have the best structural and thermal properties. In the second stage, fly ash, pyroclastic, marble powder and barite have been doped to the these selected mixtures. The obtained composite based PCM's structural and thermal properties have been analysed by using DSC, FT-IR, TGA and SEM techniques.
Phase change materials and applications
Keywords: Kimya